2020
DOI: 10.5815/ijeme.2020.02.02
|View full text |Cite
|
Sign up to set email alerts
|

A Web Based Automated Tool for Course Teacher Evaluation System (TTE)

Abstract: For any educational institution course or teacher evaluation is an integral part for the betterment and effective education system. Student's feedback could be taken as one of parts of teacher evaluation. This paper has tried to evaluate the effectiveness of the course teacher evaluation system from the students' feedback of their corresponding courses. At Stamford University Bangladesh currently the teacher's evaluation task is running by manually which is very time consuming, slow and a lengthy process. It a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 4 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…The results of the Reliability Analysis made possible to construct indices Q and Q1-Q5, as well as expanded the possibilities of data analysis: at the level of individual indicators of the complete model and the total index Q, as well as at the level of particular models and corresponding indices Q1-Q5. For example, the model Guarantee (Q4) has a partial meaningful correspondence with the model of quality of teaching disciplines [7] or evaluation of course teachers [17].…”
Section: Research Resultsmentioning
confidence: 99%
“…The results of the Reliability Analysis made possible to construct indices Q and Q1-Q5, as well as expanded the possibilities of data analysis: at the level of individual indicators of the complete model and the total index Q, as well as at the level of particular models and corresponding indices Q1-Q5. For example, the model Guarantee (Q4) has a partial meaningful correspondence with the model of quality of teaching disciplines [7] or evaluation of course teachers [17].…”
Section: Research Resultsmentioning
confidence: 99%
“…The study also chose a combination of quantitative and qualitative approaches, with the difference that the authors not only developed an evaluation model but also further analyzed the incentive mechanism and evaluation optimization mechanism of the teacher group. Amjad and Linda [29] argues that ''people-oriented'' should be whole process of evaluation, advocates the establishment of a human-oriented evaluation concept, develops dynamic and flexible evaluation indexes that reflect the developmental nature of teachers, and establishes a teaching evaluation system with full participation and full management. In Canales and Maldonado [30], under the guidance of developmental values, it is advocated to adopt the evaluation model with diversified subjects and evaluation methods and to develop evaluation indexes that reflect teachers' professional development and personality development, with the aim that the system not only detects the quality of teachers' teaching but also further promotes teachers' development.…”
Section: Related Discussionmentioning
confidence: 99%
“…Guo et al [5] reported an analysis of the satisfaction data of an Australian university for 11 consecutive semesters of information technology graduate programs [5]. Amjad and Linda [6] evaluate the effectiveness of the course teacher evaluation system from students' feedback on the corresponding courses [6]. Jin [7] constructed the evaluation index system of the microlecture teaching team for the first time by consulting a large amount of data [7].…”
Section: Related Workmentioning
confidence: 99%